2019
DOI: 10.3390/ijms20246342
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Cell-Derived Granulocyte-Macrophage Colony-Stimulating Factor Is Dispensable for the Progression of 4T1 Murine Breast Cancer

Abstract: We previously reported that 4T1 murine breast cancer cells produce GM-CSF that up-regulates macrophage expression of several cancer promoting genes, including Mcp-1/Ccl2, Ccl17 and Rankl, suggesting a critical role of cancer cell-derived GM-CSF in cancer progression. Here, we attempted to define whether 4T1 cell-derived GM-CSF contributes to the expression of these genes by 4T1tumors, and their subsequent progression. Intraperitoneal injection of anti-GM-CSF neutralizing antibody did not decrease the expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…For example, Jang et al recently identified that TNBC cells induce inflammasome activation and the M1‐type of macrophage polarization via soluble CD44 (Jang et al, 2020). Likewise, the secretion of colony stimulating factor 1 by TNBC cells is reported to be responsible for induction of iNOS in macrophages (Lin et al, 2010) Moreover, inhibition of glycolysis in TNBC cells suppressed granulocyte‐macrophage colony‐stimulating factor expression (W. Li et al, 2018), which also participates in monocyte maturation by stimulating MCP1/CCL2 (Tanimoto et al, 2008; Yoshimura et al, 2019). The inflammatory microenvironment is a common feature in breast cancer, and high expressions of glycolysis genes in patients with breast cancer are correlated with immune infiltration (W. Li et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Jang et al recently identified that TNBC cells induce inflammasome activation and the M1‐type of macrophage polarization via soluble CD44 (Jang et al, 2020). Likewise, the secretion of colony stimulating factor 1 by TNBC cells is reported to be responsible for induction of iNOS in macrophages (Lin et al, 2010) Moreover, inhibition of glycolysis in TNBC cells suppressed granulocyte‐macrophage colony‐stimulating factor expression (W. Li et al, 2018), which also participates in monocyte maturation by stimulating MCP1/CCL2 (Tanimoto et al, 2008; Yoshimura et al, 2019). The inflammatory microenvironment is a common feature in breast cancer, and high expressions of glycolysis genes in patients with breast cancer are correlated with immune infiltration (W. Li et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…G-CSF and GM-CSF have been discovered to be the main regulators of the proliferation and differentiation of myeloid cells ( 56 ). A recent study demonstrated that cancer cell-derived GM-CSF serves a key role in cancer progression, and GM-CSF is indispensable for the tuning of the tumor microenvironment and MDSCs ( 57 ). Furthermore, the inflammatory microenvironment in cancer, which is established by multiple inflammatory factors, recruits and activates MDSCs ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…Yoshimura et al identified GM-CSF derived from 4T1 cells as an important inducer of CCL2 expression in macrophages (66). They also recently reported that GM-CSFdeficient tumor cells did not show retarded growth rates and had no effect on overall CCL2 expression levels in 4T1 tumor tissue, indicating that non-myeloid-cell-derived CCL2 is also influenced by GM-CSF deletion (21).…”
Section: Influence Of Ccl2 On Tams In Cooperation With Multiple Signaling Moleculesmentioning
confidence: 99%
“…Hsu et al. studied miR-122, an anti-inflammatory microRNA, and found that its inhibition induced activation of RelB and subsequent release of pro-inflammatory chemokines, including CCL2, by macrophages ( 21 ). Long non-coding RNA LNMAT1 was shown to epigenetically activate the CCL2 gene by attracting hnRNPL to the CCL2 promoter, leading to histone trimethylation ( 22 ).…”
Section: Non-coding Rnas Involved In Ccl2 Regulationmentioning
confidence: 99%
See 1 more Smart Citation